Military Power : Explaining Victory and Defeat in Modern Battle - Biddle, Stephen D. (New Delhi Manas Publications, 2005)
"This book provides a systematic account of how force employment interacts with materiel to produce real combat outcomes. Stephen Biddle argues that force employment is central to modern war, becoming increasingly important since 1900 as the key to surviving ever more lethal weaponry. Technological change produces opposite effects depending on how forces are employed; to focus only on material is thus to risk major error - with serious consequences for both policy and scholarship." "Biddle provides a systematic account of force employment's role and shows how this account holds up under rigorous, multimethod testing. The results challenge a wide variety of standard views, from current expectations for a revolution in military affairs to mainstream scholarship in international relations and orthodox interpretations of modern military history.
Include Notes and Index
Keywords: Deployment (Strategy) -- Offensive (Military science) -- Defensive (Military science)